STUDENTS’ PERCEPTIONS TOWARD THE USE OF INSTAGRAM FOR LEARNING ENGLISH WRITING - Margareth, Margareth; Susilawati, Endang (FKIP - Universitas Tanjungpura, 2026)
Research into the use of Instagram for learning writing has mostly focused on how Instagram was used by teachers to improve students’ writing skills rather than how it is used by students in self-directed learning. To fill this gap, this research aimed at uncovering students’ perceptions towards Instagram for learning writing skills in their natural settings without any intervention to any variables. The data were derived from Likert Scale questionnaires distributed to 53 students and interviews with selected students. The data revealed that the students tended to have positive perceptions toward: 1) caption and photo feature (M=4.06), 2) Instagram social media interaction (M=3.81), and 3) Instagram direct message (M=3.89) to learn English writing. The students believed that they could explore ideas, learn vocabulary, and grammar through the caption and photo feature. They added that interactions through comment and direct message feature on Instagram allowed them to exchange ideas and promote their writing skills. The research also revealed that the students could receive feedback to correct the mistakes in grammar and vocabulary from other online users although it happened occasionally.